WEICHSELIAN GLACIATION OF THE TAYMYR PENINSULA, SIBERIA - Hjort C.; Möller P.; Alexanderson H. (My University, 2004)
During recent years there has been a re-assessment of the glacial history of the Russian Arctic, from the Kola Peninsula in the west to the Lena Delta and beyond in the east. In this context, work has been carried out on the northwestern and central parts of the Taymyr Peninsula. This chapter discusses the results regarding the glacial and marine history of Taymyr, in chronological order, and with reference to previous Russian work. Three main phases of Weichselian glaciation of successively decreasing amplitude have been mapped and dated in the chapter. The ice sheets that covered the Taymyr Peninsula on all three occasions during the Weichselian emanated from the Kara Sea continental shelf, from which they advanced generally southeastwards across the land. The Kara Sea ice sheets dammed large glacial lakes, filling the lake- and river basins both north and south of the Byrranga Mountains and, during the final stages of the different deglaciations, also lowland areas along the coast.